2004
DOI: 10.1038/sj.hdy.6800550
|View full text |Cite
|
Sign up to set email alerts
|

Mating system, sex ratio, and persistence of females in the gynodioecious shrub Daphne laureola L. (Thymelaeaceae)

Abstract: Although in gynodioecious populations male steriles require a fecundity advantage to compensate for their gametic disadvantage, southern Spanish populations of the long-lived shrub Daphne laureola do not show any fecundity advantage over hermaphrodites in terms of seed production and early seedling establishment. By using allozyme markers, we assess the mating system of this species in five populations differing in sex ratio, and infer levels of inbreeding depression over the whole life cycle by comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 46 publications
3
57
0
1
Order By: Relevance
“…Whether or not limit cycles do occur in populations is not known, because of a lack of suitable observations, but, as postulated by Gouyon et al (1991) the high variation in female frequencies observed in some gynodioecious species could reflect such dynamics (for example, Dommée et al, 1978;Wolfe and Shmida, 1997;Graff, 1999;McCauley et al, 2000;Bailey, 2002;Asikainen and Mutikainen, 2003;Delph and Mutikainen, 2003;Barr, 2004;Murayama et al, 2004;Medrano et al, 2005). However, since our results showed that the approach of point equilibria was usually slow, even without a predicted limit cycle, populations displayed wide variations of female frequencies.…”
Section: Cost Of Restorationmentioning
confidence: 51%
“…Whether or not limit cycles do occur in populations is not known, because of a lack of suitable observations, but, as postulated by Gouyon et al (1991) the high variation in female frequencies observed in some gynodioecious species could reflect such dynamics (for example, Dommée et al, 1978;Wolfe and Shmida, 1997;Graff, 1999;McCauley et al, 2000;Bailey, 2002;Asikainen and Mutikainen, 2003;Delph and Mutikainen, 2003;Barr, 2004;Murayama et al, 2004;Medrano et al, 2005). However, since our results showed that the approach of point equilibria was usually slow, even without a predicted limit cycle, populations displayed wide variations of female frequencies.…”
Section: Cost Of Restorationmentioning
confidence: 51%
“…However, empirical data suggested that the fecundity of dioecious plants at a flowering event was lower than the required value (Asikainen & Mutikainen, 2003; Ibarra‐Manriquez & Oyama, 1992; Medrano et al, 2005). Smaller size at the onset of flowering may enhance reproductive success over a lifetime by increasing reproductive opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…In natural plant populations, disease incidence is often both spatially and temporally heterogeneous, with pathogens only persisting at the metapopulation level [52][53][54][55]. Spatial variation in sex ratio has also been observed in many different gynodioecious species [56][57][58][59][60] and there is good reason to believe that, in many species, metapopulation dynamics play a large role in the maintenance of gynodioecy [56,61,62]. McCauley & Taylor [63] showed that once among population differences in sex ratio are established, females can be maintained at the metapopulation-level through frequencydependent selection, and can persist even in the absence of fertility advantages or costs.…”
Section: Discussionmentioning
confidence: 99%